Cobalt and inorganic cobalt compounds - Kim, James H; Gibb, Herman J; Howe, Paul (WHO, 2006)
Cobalt is a naturally occurring element with a number of radioactive isotopes. It is a silvery grey solid at room temperatures. Sources of exposure are both natural and anthropogenic with the largest source of exposure to the general population is through the food supply. This Concise International Assessment Document (CICAD) evaluates the scientific literature on the health and environmental effects of cobalt and cobalt compounds based on selected national and regional evaluations. This CICAD focuses on the stable isotopes of cobalt rather than radioactive ones.
Concise international chemical assessment document, ISSN 1020-6167 69
Keywords: environmentální vědy; kobalt; toxikologie; vystavení vlivu životního prostředí; Cobalt; Environmental Exposure; Risk Assessment; hodnocení rizik